Morphosyntactic and Semantic Analysis of Balochi Verbs - Ahmad, Khursheed; Khan, Safar; Ali, Zahid; Ahmed, Shahbaz (University of Chitral Journal of Linguistics and Literature, 2023)
Morphology is broader field of linguistics that studies the structure of words, forms of words and word-formation processes (Zeller, 2001; Zahid, A., 2016). Morphology studies morphemes (the smallest meaningful units of words) and how these morphemes shape words into different grammatical categories and meanings. The current study aims to explore the properties of Balochi verbs in Makrani dialect, and it also tries to find how these morphemes change the form and meaning of the verbs. The current study’s main concern is to analyse and investigate the properties of Balochi morphemes and to find out how these morphemes change the meaning and form of the verbs. For this study, the data have been collected through unstructured interviews from the native participants of Balochi (speaking the Makrani dialect). The data have been analyzed through Radford’s (2009) “theory of agreement”. The study finds that Balochi, being a pro-drop language, works like English and other languages of the world where subject agrees with verb and verb with its subject. It is also found that verbs in Balochi have various properties and these properties are generalized by tense, number, mood, voice, and person.